Fitness Apps, Live Streaming Workout Classes, and Virtual Reality Fitness for Physical Activity During the COVID-19 Lockdown: An Empirical Study - Liu, Ru; Menhas, Rashid; Dai, Jianhui; Saqib, Zulkaif Ahmed; Peng, Xiang (Frontiers in Public Health, 2022)
Background Physical activity is an essential need of the human body that helps improve the physical fitness of an individual and creates a positive impact on overall wellbeing. Smartphone applications play an essential role in providing several benefits to consumers by offering various capabilities in terms of health and fitness.COVID-19 preventive measures shut down public places, and people cannot go to the gym and parks for physical activity. Smart applications for physical activity are an effective way to keep active while staying at home. Objective The objective of the present study was to assess the mediating role of the e-platforms physical activity among the Chinese people in China during the COVID-19 lockdown. Method The participants in this study were Chinese citizens living in home isolation during the early stages of the epidemic in China. The primary data was collected via an online survey using a convenience sample strategy in accordance with the study purpose. The collected data were cleaned by using the SPSS-25 statistical software. SmartPLS 3.0 software was used to investigate the suggested study framework utilizing the structural equation modeling technique. Results Descriptive statistics shows that the ratio of gender includes 49% (n = 2,626) male and 51% females in the entire sample. SEM results show that all hypotheses (H1: β = 0.497, T = 43.068, P = <0.001; H2: β = 0.498, T = 41.078, P = <0.001; H3: β = 0.498, T = 41.078, P = <0.001; H4: β = 0.471, T = 39.103, P = <0.001; H5: β = 0.468, T = 42.633, P = <0.001; H6: β = 0.251, T = 11.212, P = <0.001; H7: β = 0.367, T = 16.032, P = <0.001; H8: β = 0.170, T = 13.750, P = <0.001; H9: β = 0.125, T = 10.604, P = <0.001; H10: β = 0.173, T = 14.842, P = <0.001) were statistically confirmed. Conclusion In COVID-19, when there are limited physical activity resources, smart applications play an essential role as an alternative to gyms and change people's perspective regarding the adoption of health and fitness. Smart applications have made exercise and physical activity accessible and convenient to adopt.